Economic Community of West African States (ECOWAS) regional action plan for rice self-sufficiency by 2025 - CGIAR Research Program on Rice (2021)
Regional initiatives and all the countries' focal points presented their support to the rice sector and achievements made in the 10 years . During the first phase, supported by AfricaRice, the Central Agricultural Research Institute trained 178,000 farmers on Good Agronomic Practices, and trained 137,281 beneficiaries through farmers’ business school.